2016
DOI: 10.1016/j.recqb.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

BIOSORPTION OF CD, CR, MN, AND PB FROM AQUEOUS SOLUTIONS BY Bacillus SP STRAINS ISOLATED FROM INDUSTRIAL WASTE ACTIVATE SLUDGE

Abstract: Nota: Artículo recibido el 04 de mayo de 2015 y aceptado el 30 de enero de 2016. ARTÍCULO ORIGINAL aBstraCtThe microorganisms are capable of accumulating heavy metal ions from water as biosorbent agents, offering a potential alternative for the detoxification and recovery of toxic/precious metals in industrial wastewater.In the present work, metal-resistant bacterial strains were isolated and identified from activated sludge of a waste treatment plant in the Municipality of Santa Rosa Jauregui, Querétaro. To o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 24 publications
2
20
1
1
Order By: Relevance
“…The discharge of heavy metals through various man-made activities, for example excessive application of chemical fertilizers, wood burning, coal combustion, vehicle exhaust, mining, smelting and incineration [2], has caused a wide spread disruption of the normal biogeochemical cycles of metals causing a larger accumulation of heavy metals in the environment, especially the soil [6][7][8]. The major heavy metals of concern include lead, cadmium, arsenic, mercury, copper and chromium because of their toxic impact on human health; for instance, environmental exposure to high concentrations of heavy metals has been linked with various cancers and kidney issues [9]. Heavy metals have also greatly affected soil microorganisms and plants growth and development [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discharge of heavy metals through various man-made activities, for example excessive application of chemical fertilizers, wood burning, coal combustion, vehicle exhaust, mining, smelting and incineration [2], has caused a wide spread disruption of the normal biogeochemical cycles of metals causing a larger accumulation of heavy metals in the environment, especially the soil [6][7][8]. The major heavy metals of concern include lead, cadmium, arsenic, mercury, copper and chromium because of their toxic impact on human health; for instance, environmental exposure to high concentrations of heavy metals has been linked with various cancers and kidney issues [9]. Heavy metals have also greatly affected soil microorganisms and plants growth and development [10].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of heavy metals in the environment has been a source of concern over the past few decades due to their persistence, potential harm and toxicological hazards [2]. Besides the fact that they are non-biodegradable, they may also undergo microbial or chemical transformation [8,9,11,12]. Recently, Hasani et al [13] and Nath et al [3] reported that heavy metal polluted environments activate co-selection process and cause a decrease in microbial tolerance to antibiotics due to their ability to co-regulate genes responsible for antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The pH of the initial solution determined the charge on the surface of adsorbent and the degree of ionization and speciation of the metal ion. 39 The effect of pH on the adsorption of Cr(VI) was evaluated by changing the initial pH from 2 to 11. According to Fig.…”
Section: Characterization Of Aerogelmentioning
confidence: 99%
“…In order to determine the Pb (II) remotion kinetics, batch-type experiments were carried out at 150rpm, by contacting different initial metal concentrations (25,50,75, 100 mg L -1 ) for the unmodified lemon peel pretreated with citric acid.The experiments were performed at pH 3, which was adjusted by adding drops of NaOH or HCl 0.1 N and 0.5 % w v -1 , respectively; and a ratio of 2 g L -1…”
Section: F Adsorption Kineticsmentioning
confidence: 99%